EFFECTIVENESS OF ABRASIVE FLOW MACHINING ON ADDITIVELY MANUFACTURED PARTS WITH VARYING CROSS-SECTION GEOMETRIES - Eyercioglu, Omer; Akeloglu, Mehmet Ali (International Journal of Research -GRANTHAALAYAH, 2025)
Additive manufacturing has become an important production method nowadays and thanks to the developments in this field, it makes it possible to manufacture complex parts with new practical properties. Although additive manufacturing methods make it possible to produce parts with complex geometries, parts produced with additive manufacturing usually have surfaces with a high degree of roughness. Because of the negative effects on the part’s fatigue life and stress concentration caused by this rough surface, it limits its usage in industrial applications. To enhance their surface quality, these parts require post-processing. However, this post-processing enhancement cannot be performed with conventional methods due to the complex geometry of the parts produced with additive manufacturing methods. That is why, the abrasive flow machining (AFM) process which, is an option with better results in the surface finishing of AM parts, is used to improve the surface characteristics. On the other hand, in the abrasive flow machining (AFM) process, the effectiveness of material removal tends to decrease in corner regions, particularly when the flow channel geometry involves sharp-edged profiles such as square or hexagonal shapes. In the study, Poly Lactic Acid (PLA) parts produced with Fused Deposition Modeling (FDM) technique in square, hexagonal and cylindrical sections created in the same volume were produced and subjected to AFM process and surface improvements on the corners and edges were observed. This study aims to demonstrate, through both analytical and experimental approaches, that the efficiency of the AFM process is reduced at the corners of such geometries while overall surface quality is improved. Furthermore, solution-oriented recommendations are proposed based on the analytical evaluations to enhance process performance in these critical regions.